Approaches of improving food allergy knowledge: Children with food allergy’s quality of life - Din, Norrina; Rashid, Basri; Ramli, Kamal Izzuwan; Othman, Che Noriah (e-International Publishing House Ltd, United Kingdom, 2018)
Food allergy commonly affects many people, including children regardless of their age. Their life could be threatened if they are exposed to food allergen. Therefore, nursery employees need to take extra precaution when dealing with children with food allergy compared to ordinary children. Thus, this paper warrants to assess the knowledge of caretakers of children with food allergy and determines the approaches needed to improve their knowledge on how to manage this susceptible population.